Bathymetric Survey Using Singlebeam Echosounder for Calculation of Dredging Volume in Pertamina IV Cilacap Port Channel - Kusmantoro, Yeri; Harsono, Gentio; Trismadi, Trismadi; Fatoni, Khoirul Imam (Formosa Journal of Science and Technology, 2024)
The TUKS 60 Cilacap Port area is facing significant challenges due to sedimentation that causes the approach channel to silt up, thereby disrupting navigation and ship operations. This study identifies the depth distribution, assesses the quality of the bathymetric survey, and calculates the volume of dredged material needed to maintain a channel depth of 8 meters below the chart datum. The method used is a bathymetric survey using the Odom Hidrotrac II Singlebeam Echosounder (SBES), geodetic data from CORS-based GPS, and tidal correction from Low Water Spring. (LWS). Data processing was carried out using Hypack 2015 software and the average end area method for volume calculation. Survey data were validated using the criteria from the International Hydrographic Organization (IHO) S-44 Edition 6.1.0 standard. (2020). The results show a depth ranging from -1.2 meters to 10 meters, with 95.8% meeting the exclusive and special order criteria. The volume of dredging required to reach the design depth is 159,991 m³. These findings support dredging planning while ensuring navigational safety and operational sustainability of the port, demonstrating the reliability of SBES technology, Hypack 2015, and compliance with IHO validation for the dredging plan.